Transnational Europe
X, 271 p.
Keywords: Transnational connections are a defining feature of contemporary Europe. They include cross-border economic and cultural exchange, migration, and political activism. This volume probes their political and social significance and makes a case for incorporating transnationalism more systematically into the research agenda of European Studies.